Why did the Ottoman Empire not Become Capitalist, according to Sabri F. Ülgener - Elif Türkislamoğlu (İstanbul İktisat Dergisi)
Sabri F. Ülgener (1911– 1983) was among the foremost intellectuals in the history of Turkish thought. He focused on the study of culture and the sociology of religion, building on his achievements in his first field of study, economics, and investigating the question of mentality in Ottoman-Turkish history. Ülgener is distinguished from others in Turkish thought for his pursuit of the question why the Ottoman Empire did not become capitalist, inspired by the relationship that the German thinkers Werner Sombart and Max Weber proposed between capitalism, the mentality of a society, and religion. Ülgener took the period at which the empire reached the pinnacle of its power, while capitalism began appearing in the West as the historical moment of this study. He addressed the question both in terms of economic mores and overall social mentality. While Ülgener worked on this question, he also developed an analysis of both the economic morality and mentality of Medieval Ottoman society and a sociology of religion. In this study, after drawing Ülgener’s portrait as a thinker, we present and analyze the way that Ülgener discussed the Ottoman Empire’s social and economic structure in pursuing the question of why the Ottoman Empire did not become capitalist, based on his world of thought and its sources.